Unsur-unsur Kefilsafatan dalam Buku "Butir-butir Budaya Jawa" - Sutrisno, Slamet (Jurnal Filsafat "WISDOM", 1999)
This research investigated the book of "Butir-butor Budaya Jawa" 1990, 205p. The aim of this study is to sound out the possibility of transforming the philosophical values of this book to the course of branch of philosophy, that is, Metaphysic/Ontology, Epistemology, and Logic: Ethics. This research also studied the specific contens of philosophy, for example are the philosophy of social and politics:: philosophy of laws; philosophy of man and theodiceae. Feurtheremore, it will try to estimate some contents of system of philosophy in order to express the implicit tenets of Javanese culture.This research will be able to give two important benefits covered the development and academic benefit. Firstly, on the scope national development this research will support a reference of national ethos and development ethics. Secondly, in term of academic knowledge, it can expand the contens of philosophy of culture and Indonesian or Pancasila philosophy.This research emphasize on the literacy study which analysis data carried out by qualitative method by applying the hermeneutics-interpretation concerning the text.The research findings show that the six themes--Belief in the Supreme God; Spirituality; Humanity; Nationhood; and On malerial Goods--contained the three elements of philosophy mentioned above. The book also expressed the naunce of several specific philosophy, tenets of wisdom and also the elements of existentialistic and pragmatic thought/ The three elements of philosophy were not made up separated form to show some interrelation so that expressed the whole of Javanese tenets.